KINERJA PENYULUH KEHUTANAN DI KESATUAN PENGELOLAAN HUTAN (KPH) TANAH LAUT - Astri Belinda Nur Asrifa; Asysyifa Asysyifa; Hafizianor Hafizianor (Jurnal Sylva Scienteae, 2022)
The aims of this research was to analyze the level of foresty intructor performance in KPH Tanah Laut and to analyze the factors that affect the level of foresty intructor performance in KPH Tanah Laut. The research method used is saturation sampling method. Saturation sampling method is the sampling method with entire population. The data was collected by interview and distributing questionnaires as primary data and secondary data of information from journals, report or data from related intitute. The result showed that the performence of forestry intructor in KPH Tanah Laut based on an assessment of 7 criteria (Employee Administration, The Condition of Working Area, The Planning, The Forestry Conseling Activity, Result and Impact of the Forestry Conseling Activity, Monitoring, Evaluation and Reporting, and Development Activities of the Supporting Profession) overall got a “good” level of performance with score of 60,45. Meanwhile, for each respondent such as respondent 1, the performance level was "enough" with a score of 57.88, respondent 2 received a "good" performance level with a score of 67.24 and respondent 3 received a performance level "enough” with a value of 56.24. The factors that influence the level of performance of the forestry instructor in the Tanah Laut KPH are age, education and competence, motivation and independence, and the scope of the forestry instructor's work areaPenelitian ini bertujuan menganalisis tingkat kinerja penyuluh kehutanan di KPH Tanah Laut dan menganalisis faktor-faktor apa saja yang mempengaruhi tingkat kinerja penyuluh kehutanan di KPH Tanah Laut. Metode penelitian menggunakan metode sampling jenuh. Metode sampling jenuh adalah metode pengambilan sampel dengan seluruh populasi. Pengumpulan data dilakukan dengan wawancara dan pembagian kuesoner sebagai data primer dan data sekunder berupa informasi dari jurnal, laporan, atau data dari instansi terkait. Hasil penelitian menunjukkan kinerja penyuluh kehutanan di KPH Tanah Laut berdasarkan penilaian dari 7 kriteria (Administrasi Kepegawaian, Kondisi Wilayah Kerja/Binaan, Perencanaan, Kegiatan Penyuluhan, Hasil dan Dampak Kegiatan Penyuluhan, Pemantauan, Evaluasi Dan Pelaporan, dan Kegiatan  Pengembangan Profesi Penunjang) secara keseluruhan mendapat tingkat kinerja “bagus” dengan nilai 60,45. Sedangkan untuk masing-masing responden seperti responden 1 mendapat tingkat kinerja “cukup” dengan nilai 57,88, responden 2 mendapat tingkat kinerja “bagus” dengan nilai 67,24 dan responden 3 mendapat tingkat kinerja “cukup” dengan nilai 56,24. Faktor-faktor yang mempengaruhi tingkat kinerja penyuluh kehutanan di KPH Tanah Laut yaitu usia, pendidikan dan kompetensi, motivasi dan kemandirian, serta cangkupan wilayah kerja penyuluh kehutanan.